The experimental behavior and simple modeling of joints in composite MRFs. (15th December 2015) - Pecce, M.; Rossi, F.
Graphical abstract: Highlights: Two steel-concrete composite joints (welded and bolted) were tested. Ductility, energy dissipation and stiffness degradation were investigated. The principal role of the composite beam is highlighted. An "equivalent" plastic hinge for the composite beam was evaluated. A mono-dimensional model was implemented and compared with the experimental results. Abstract: In the case of composite steel-concrete construction, the seismic performance of Moment Resisting Frames (MRFs) is not well-known as for reinforced concrete or steel construction because the coupling of the two materials results in different mechanisms with asymmetric behaviors in the case of reversed loads. The performance of the frames under seismic actions is dependent on all components, beams, columns and joints. However, the modern approach of the international codes (Eurocode) consists of a hierarchy of resistances governing the failure mode, i.e., the ductility of the structure. To contribute to a better understanding and assessment of the actual behavior of steel-concrete composite joints, this paper discusses the experimental results of two full-scale steel-concrete composite joints (a welded and a bolted joint) tested under cyclic loading. The two full-scale composite exterior joints were designed to localize the damage at the composite beam end with respect to the designed capacity of the MRFs. Therefore, the joints contribute to the deformability of the system in the elastic field. The specimens were highly instrumented; the experimental results are presented in terms of global and local measures. For the global response, the main role of the composite beam is highlighted. The performance of the joints is described in terms of resistance, ductility, dissipated energy and stiffness degradation. The contribution of the composite beam to the global ductility is evaluated in terms of rotational capacity, and an "equivalent" plastic hinge length is evaluated. A simple model for the estimation of the nonlinear behavior of the joints, which is suitable for analyzing the global behavior of framed composite structures, is proposed.